KERUKUNAN UMAT BERAGAMA DI KABUPATEN TULANG BAWANG PROVINSI LAMPUNG - Bashori A. Hakim (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2012)
This interesting study on harmony of people who have diffrent religions was done in district of Tulang Bawang, the province of Lampung. This research is more interesting since there are so many social conflicts have been happened in other regions. The people who stay in the district are relatively heterogen in terms of religions and ethnicity. So actually they have tendency to be in conflicts. This study traces the harmony of life among people who are in different religions. From that 2011 research which was done qualitatively is found that those people are condusive. This condition is caused by there are attitude of tolerance, respect others feeling that they live togetherly. Beside that, there are also local culture and local wisdom make them live in harmony.